Investigation on the Potential Application of MSWI Bottom Ash as Substitute Material in Portland cement Concrete (International Journal of Scientific Research in Science and Technology, 2025)
This study investigates the potential use of municipal solid waste incineration (MSWI) bottom ash as a sustainable component in cement-based materials. The growing demand for sustainable construction materials necessitates exploring alternative resources that reduce environmental impact. Municipal solid waste incineration (MSWI) bottom ash is a promising substitute for conventional materials in Portland cement concrete, offering benefits such as waste minimization, conservation of natural aggregates, and reduced energy consumptionThis research focuses on characterizing the physical and chemical properties of MSWI bottom ash and assessing its effects when used as a partial replacement for cement and fine aggregate in cement paste and concrete. This study evaluates the potential of MSWI bottom ash as a partial replacement for cement and fine aggregates in concrete. The physical, chemical, and mechanical properties of MSWI bottom ash were characterized, and its impact on cement hydration and concrete performance was analyzed. Results indicate that MSWI bottom ash enhances cement hydration due to the presence of calcium oxide, calcium sulfate, and silica dioxide. However, volume expansion caused by hydrogen gas evolution necessitates proper treatment and proportioning to ensure performance stability. This paper highlights the opportunities and challenges of incorporating MSWI bottom ash in sustainable concrete production.